COVID-19 pneumonia in a multiple sclerosis patient with severe lymphopenia due to recent cladribine treatment. (September 2020) - Dersch, Rick; Wehrum, Thomas; Fähndrich, Sebastian; Engelhardt, Monika; Rauer, Sebastian; Berger, Benjamin
Background: Most cases of COVID-19 are considered mild, but patients with immunosuppressant treatment might be prone to severe courses of disease. Expert panels advise to delay treatment with cell-depleting MS therapies during the COVID-19 pandemic. Methods: We report a case of a patient with relapsing-remitting multiple sclerosis who developed COVID-19 pneumonia 2 weeks after the first week of cladribine therapy. Results: Despite a severe lymphopenia (absolute lymphocyte count 240/µL), the patient had a moderate course of COVID-19. Conclusion: Apart from maximal supportive treatment, this could be due to cladribine reducing inflammatory response, which probably contributes considerably to severe courses of COVID-19 pneumonia.